SVI Self-Study Guide: A Study Tool for Independent Preparation for the AAMC Standardized Video Interview - Ilana Mayer-Hirshfeld (Association of American Medical Colleges, 2019)
Introduction Since 2017, students applying to emergency medicine residencies must take the AAMC Standardized Video Interview (SVI) to assess their knowledge of professional behaviors and interpersonal and communication skills. Due to the SVI's novelty, there are not many study tools available to prepare for it, outside of the resources provided by the AAMC. Methods The SVI Self-Study Guide is a PowerPoint document that learners can use to prepare for the SVI independently. It is intended for fourth-year medical students who are applying to emergency medicine residencies and therefore planning to take the SVI. The guide was distributed via email and assessed with a pre- and postquiz measuring subjective feelings of preparedness as well as testing knowledge of professionalism and interpersonal and communication skills. Results Eleven students were invited to use the SVI Self-Study Guide, of whom 10 and eight took the pre- and postquiz, respectively. There was a statistically significant increase in learners' self-rated feelings of preparedness to take the SVI (p < .05). Although there was no significant change in the average score on four knowledge-based questions (p = .29), the average score increased from 72.50% to 93.25%. Discussion Overall, there was a higher improvement in feelings of preparedness to take the SVI than in performance on knowledge-based questions. This suggests that learners benefited the most from practicing using the SVI testing format. The SVI Self-Study Guide can be distributed via email to supplement existing resources in preparing for the SVI.